‘Anthropologists of our own experience’: Taxonomy and Testimony in The Museum of Innocence and The Virgin Suicides - Clare Hayes-Brady (Angles)
The narrators of Jeffrey Eugenides’ The Virgin Suicides (1991) and Orhan Pamuk’s The Museum of Innocence (2008) spend their time obsessively gathering, curating and categorising objects associated with the objects of their affection. Talking about his novel, Pamuk argued that “the desire to gather objects is central to the human heart”, and in both of these novels, the male narrators react to the deaths of their beloveds by memorialising them in the form of object collections. The collections — one a group of “exhibits” and one a catalogue of the contents of a museum — serve both as a reminder of the beloved(s) and as a narrative aid, and are displayed to the unspecified “You”, the witness of the boys’ investigation in The Virgin Suicides and the museum visitor in The Museum of Innocence. In both cases, the collections are held up for investigation by the reader as proof of the narrator’s love. Both narrators obscure the subjectivity of their beloveds by confining them to the sum of the objects collected, presenting an essentially narcissistic projection of the self on to a muted, virginal other. I argue that the obsessive need for testimony demonstrated by both narrative voices reflects a fundamental incapacity to see the female other as a subject, drawing the reader, as witness, into the position of voyeur. By offering a post-mortem memorialisation of this kind, the narrators appropriate the image of their beloved(s), re-presenting them as objects among objects, albeit still the object of mystery and obsessive fascination. Exploring the use of visual touchstones (fictional in The Virgin Suicides, but real in The Museum of Innocence, which opened in Istanbul in 2009), I take Stanley Cavell’s idea of acknowledgement and Judith Butler’s theory of mournable lives to discuss memory, subjectivity and power in the recollection of the beloved dead.